Anthropogenic factors of education relief within the platform-denudation plains of the arid zones of Kazakhstan (Central Kazakhstan) (Journal of Geography and Environmental Management, 2019)
In article are considered the main anthropogenic factors that determine the spatial distribution and dynamics of the negativeprocesses of morphogenesis within the platform-denudation plains of Central Kazakhstan, characterized by an arid – climate conditions